Effect of replacement therapy (CRRT) and hemodialysis (IHD) on severe acute renal failure - Xiangyuan Zhang; Yinfang Yuan (Frontiers Media S.A., 2023)
Hyperkalemia, metabolic acidosis, and acute uremia are the main symptoms in patients with severe acute renal failure (SARF). Its clinical symptoms are obvious, and it is extremely harmful. It needs to take active and effective measures for treatment. CRRT refers to any extracorporeal blood purification treatment technique designed to replace impaired renal function for 24 h or nearly 24 h. Hemodialysis treatment is a treatment process in which the patient's blood is discharged from the body, passes through the dialysis membrane and dialysis machine, removes excess toxins and water in the body, corrects electrolyte and acid-base disorders, and then returns the blood to the body. In order to explore the efficacy of replacement therapy and hemodialysis in the treatment of severe acute renal failure, the data samples were randomly divided into observation group and control group, who were given conventional treatment, hemodialysis and replacement therapy, respectively. Clinical data show that after replacement therapy and hemodialysis in patients with severe acute renal failure in the observation group, the levels of parathyroid hormone, renin, and quality of life were all improved, with an improvement rate of 9.47%, which has certain promotional value.